2020
DOI: 10.35860/iarej.735529
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of consistency limits of fine-grained soils via regression analysis: A special case for high and very high plastic clayey soils in Istanbul

Abstract: Consistency limits are essential and simple design parameters that are utilized as standard entries of all kinds of soil investigation programs conducted for geotechnical projects which are constructed in/on fine grained soils. These limits also represent mineralogical and physical properties of clayey soils directly and used to estimate their strength and rigidity properties indirectly. However, the consistency tests are assumed as the simple and basic tests of geotechnical engineering investigations, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Further, compared to conventional consistency limits testing apparatuses, spectroscopy equipment is not as readily available or robust. For intermediate to extremely-high plasticity clays from Istanbul Province (Turkey), Akbay Arama et al [85] reported relatively strong correlations, obtained from power regression analysis of a very large database (1523 LL tests), for evaluating the values of I P(PC) directly from only LL PC test results. However, with a wide variety of clay soils inevitably present in such a large deposit, as evident from the huge scatter of the experimental data, plotting from the A-line up to the U-line in the Casagrande-USCS plasticity chart, it is evident that the reported correlation could not consistently produce reliable I P(PC) predictions, for subsequent use in deducing design parameter values from existing correlations based on I P(PC) data.…”
Section: Recent Developments Regarding Consistency Limits Determinations and Soil Classificationmentioning
confidence: 99%
“…Further, compared to conventional consistency limits testing apparatuses, spectroscopy equipment is not as readily available or robust. For intermediate to extremely-high plasticity clays from Istanbul Province (Turkey), Akbay Arama et al [85] reported relatively strong correlations, obtained from power regression analysis of a very large database (1523 LL tests), for evaluating the values of I P(PC) directly from only LL PC test results. However, with a wide variety of clay soils inevitably present in such a large deposit, as evident from the huge scatter of the experimental data, plotting from the A-line up to the U-line in the Casagrande-USCS plasticity chart, it is evident that the reported correlation could not consistently produce reliable I P(PC) predictions, for subsequent use in deducing design parameter values from existing correlations based on I P(PC) data.…”
Section: Recent Developments Regarding Consistency Limits Determinations and Soil Classificationmentioning
confidence: 99%
“…Moreover, the components in the parallel system may contain certain defects, such as cracks or holes. These defects can cause mutual influence on the performance degradation of each component (Hsu and Shu, 2010;van Noortwijk, 2009;Arama et al, 2020). Therefore, the time-varying reliability evaluation of mechan-ical parallel systems with performance degradation of components becomes extremely complicated due to the complex failure dependence among components.…”
Section: Introductionmentioning
confidence: 99%